Effect of forest disturbance on the diversity and composition of odonata in Kalabakan safe project site, Tawau, Sabah - Aqilah Afendy (2017)
Forest clearance usually affects the habitat and the diversity of certain species, from good to bad, including the Odonates that usually need clean water to breed. Conversion of the forest such as fragmentation and forest degradation may lead to changes in water quality. The aims of this study were: 1) to study the diversity and composition of Odonata at three different types of forest which are Old Growth Forest (OG), Secondary Forest (SF), and Oil Palm (OP) in Kalabakan SAFE Project Site, 2) to study the effect of water quality towards the composition of odonates larvae, and 3) to study the effect of canopy cover towards the species composition of Odonata. The samplings were conducted at Kalabakan SAFE Project sites which were Sg. Virgin Jungle Reserve (VJR) to represent old growth forest; Sg. Oil Palm Selangan Batu (OPSB), and Sg. Oil Palm Gaharu (OPGHR) representing oil palm plantation; and Sg. SFl and Sg. SF2 to represent the secondary forest. Another stream at Maliau Basin Conservation Area (MBCA) was chosen to represent old growth forest together with Sg. VJR. Aerial net was used to collect adult while Surber net and D-frame net were used to collect larvae. Two stations were set for each stream (upper and lower reach) for both adult and larvae. Physical parameters ( canopy cover, pH, water temperature, dissolved oxygen, salinity and conductivity) for each station were recorded. A total of 1192 individuals of adult odonates were collected (35 species, 23 genera) while for larvae, a total of 1336 individuals (13 families) were captured. For adult, Euphaea subcostalis was the most abundant species for Zygoptera (288 individuals) and Trithemis festiva was the most abundant species for Anisoptera (244 individuals). These were abundant and common species as they can easily be found at all stations. As for the larvae, Gomphidae (Anisoptera) and Euphaeidae (Zygoptera) were dominated the streams with 613 and 396 individuals respectively. SF has the highest diversity (H'=2.2083, D=0.1410, E=0.7793) for adult because of the mixture of habitat condition where they are more canopy opening, thus attract more species of odonates. OG has the highest diversity (H'=l.516, D=0.3042, E=0.591) for larvae because of the quality of the water was better than other rivers. Biological Monitoring Working Party (BMWP) index and BMWPThai showed all types of forest have moderate water quality. The Malaysia Interim National Water Quality Standards (INWQS), also showed that all streams were classified as Class I. Ordination graph of Canonical Correspondence Analysis (CCA) showed that species from family Libellulidae were highly correlated with temperature, conductivity and salinity while the other three zygopteran species namely Heliocypha biforata, Rhinocypha humeralis and Vesta/is sp. were highly associated with canopy cover. As for larvae, family Calopterygidae and Corduliidae were highly correlated with temperature, salinity and conductivity while other families such as Platystictidae and Chlorogomphidae were correlated with canopy cover and pH level. The changes in forest habitat affected the diversity of Odonata as the composition of odonates decreased with the forest quality. The erosion and sediment that flow into the freshwater habitat affect the quality of the streams thus affected the composition of the Odonata that depends on freshwater habitat.